Fiber-Reinforced Magnesium Phosphate Cement-Based Nanocomposites in the Field of Bridge Structure Repair and Strengthening - Wenwei Yang (Advances in Materials Science and Engineering)
Currently, fiber-reinforced magnesium phosphate cement-based nanocomposites are being used in various projects. The unique physical properties of this material allow it to bear the load together with the material in the inherent structure, and it will be better used in the field of bridge structure repair and reinforcement. The purpose of this article is to study the application of fiber-reinforced magnesium phosphate cement-based nanocomposites in the field of bridge structure repair and reinforcement. Through the use of finite element analysis software and various stress sensor materials, the mechanical properties of fiber-reinforced magnesium phosphate cement-based nanocomposites are used to analyze the mechanical properties of damaged bridges in our area after reinforcement treatment and establish a control group (using magnesium phosphate cement-based nanocomposite materials) for comparative experiments. The reinforcement effect of the bridge repair structure under different ballast conditions is studied. Studies have shown that fiber-reinforced magnesium phosphate cement-based nanocomposites can provide excellent reinforcement for damaged bridge structures. Compared to the control group, the strength and stiffness of the repaired structure were significantly improved, the strength increased by 15.7%, and the stiffness increased by 12%. The carrying capacity has also been improved compared to the previous one, from the original 120 t to 150 t.